Changes in the crystal structure of SnO2 nanoparticles and improved H2S gas-sensing characteristics by Al doping - Choi, Myung Sik; Ahn, Jihye; Kim, Min Young; Mirzaei, Ali; Choi, Soon-Mok; Chun, Dong Won; Jin, Changhyun; Lee, Kyu Hyoung (ELSEVIER, 2021)
Pristine and Al-doped SnO2 nanoparticles with different amounts of Al dopant were synthesized using a conventional hydrothermal process. The existing SnO2 exhibited simple interstitial physical bonding (SnO2-Al (1:0.16)) with the Al dopant; however, with an increase in the Al concentration, the bonding changed to substitutional chemical bonding (SnO2-Al (1:0.33)). We found that this crystal structural change is strongly interrelated with surface reactivity; the optimized Al-doped SnO2 nanoparticles-based sensor exhibited a significantly improved response of 17.38 - 20 ppm H2S gas with a response time of 35 s. The enhanced gas response was related to the high surface area of the optimal gas sensor (BET surface area = 78.087 m3/g) as well as the beneficial effects of Al doping. It is highlighted that this simple technique of engineering the bonding characteristics can be widely applied to other semiconducting metal oxides.
Keywords: DOPED ZNO; SENSOR; TEMPERATURE; SHELL; TIO2